Primary non-Hodgkin lymphoma of the cecum - Kropivnik, Mateja (Radiology and oncology (Ljubljana), 2002)
Background. Primary lymphoma of the colon is rare, constituting 0.4 % of primary colonic malignancies and usually involves cecum or rectum. The aim of this paper is to present the role and the importance of double contrast bariumenema (DCBE) in the diagnostic process. Case report. A 77 years old malewas admitted because of suspected inflammation in the area of total endoprosthesis of the left hip, inserted ten years before. Listeria monocytogenes was isolated from the aspirate and the patient treated with antibiotics. Twenty years ago the patient underwent nephrectomy because of hypernephroma of left kidney. At the time of admission he had sideropenic anaemia and he was febrile. Conclusion. The patient underwent many diagnostic procedures: ultrasound (US), computed tomography (CT), double contrast barium enema, which showed a tumour in the cecum, small bowel follow-through and scintigraphy. The diagnosis of primary non-Hodgkin lymphoma was established byhistology after biopsy at colonoscopy.
Keywords: Aged; Barij; Barium; Cecal neoplasms; Cekalne novotvorbe; Contrast media; črevesje; diagnostika; Kontrastna sredstva; Lymphoma, non-Hodgkin's; novotvorbe; Ostareli; radiografija; Radiography; tumor